2009
DOI: 10.1002/macp.200800596
|View full text |Cite
|
Sign up to set email alerts
|

AB2 Functional Polyesters via Ring Opening Polymerization: Synthesis and Characterization

Abstract: Aliphatic AB2 functional polyesters were conveniently prepared by the ring opening polymerization of ε‐caprolactone and L‐lactide in the presence of the AB2 functional initiator 2,2‐bis(hydroxymethyl)propionic acid (bis‐MPA) and Sn(Oct)2 as the catalyst. In L‐lactide polymerization, both bis‐MPA hydroxyl groups initiated the polymerization reaction, but for ε‐caprolactone polymerization this depended on the monomer to initiator to catalyst ratio. Initiation at two hydroxyl groups occurred at high monomer to in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
6
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(7 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…To our knowledge, this is the first report for the preparation of HB-PLLA homopolymers with controlled branching densities, although the HB-PLLA copolymer has been reported in the literature . The AB 2 -type PLLA macromonomers were prepared by the ring-opening polymerization of a lactide initiated by 2,2-bis(hydroxymethyl)propionic acid (bis MPA) as the initiator, according to the method reported by Feijen and co-workers . The self-polycondensation of the AB 2 macromonomer (degree of polymerization of the lactide ( n ) = 5.0, 8.4, 19, 29, and 42) was then preformed in the presence of condensation agents to form high-molecular-weight branched polylactides with different branching densities.…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, this is the first report for the preparation of HB-PLLA homopolymers with controlled branching densities, although the HB-PLLA copolymer has been reported in the literature . The AB 2 -type PLLA macromonomers were prepared by the ring-opening polymerization of a lactide initiated by 2,2-bis(hydroxymethyl)propionic acid (bis MPA) as the initiator, according to the method reported by Feijen and co-workers . The self-polycondensation of the AB 2 macromonomer (degree of polymerization of the lactide ( n ) = 5.0, 8.4, 19, 29, and 42) was then preformed in the presence of condensation agents to form high-molecular-weight branched polylactides with different branching densities.…”
Section: Introductionmentioning
confidence: 99%
“…However, some limitations were still noted. For example, it was observed that in the later stages of the polymerization of LA and CL initiated by hydroxyacid (or at higher catalyst concentrations), condensation reactions with the participation of carboxyl groups originated from bisMPA occurred [110]. The undesired condensation reaction between terminal hydroxyl and carboxyl groups was also observed in the case of the cationic polymerization of LA initiated by hydroxyacids [115].…”
Section: Pla-based Macromonomers Could Be Used For Polycondensation Wmentioning
confidence: 99%
“…The latter were sometimes used with protected carboxylic groups like in the works of Trollsås, Hedrick and coworkers[107,108] and Kwak[109], who applied bisMPA (or bis(hydroxybutyric) acid, BHB) protected with benzyl alcohol for the initiation of CL polymerization with the subsequent deprotection of the carboxyl group. Sometimes, hydroxyacids were used without prior protection[110][111][112]. It seems that the protected derivative of the hydroxyacid was applied to avoid the possible interference of the free carboxyl group with the pseudoanioniccoordination polymerization active centers; polymerizations were performed with the application of Sn(Oct) 2 or Al(OiPr) 3 as catalyst at temperatures ranging from 110 to 130 °C.The obtained AB 2 -type macromonomers were then used for polycondensation, which was accomplished by esterification with the application of typical catalytic systems such as dicyclohexylcarbodiimide (DCC) / 4-(dimethylamino)pyridine (DMAP) or, in most cases, by the DCC/4-(dimethylamino)pyridine 4-toluenesulfonate (DPTS) system developed by Stupp…”
mentioning
confidence: 99%
“…One of the famous methods to improve the solubility and processability of polymers is branching. Highly branched polymers may be prepared by different strategies, particularly polycondensation of an AB 2 monomer, which is cheap and convenient and has attracted great attention [13,14]. Moreover, some HPs have been synthesized via the A 2 + B 3 synthetic method [15,16].…”
Section: Introductionmentioning
confidence: 99%